ETIKA ISLAM DAN FILSAFAT MORAL: PERSPEKTIF TEORI KEWAJIBAN DAN KEBAJIKAN - Anisa; Mursam; Nur Hamzah; Rusdi Sulaiman; Sahri (As-Sulthan Journal of Education, 2025)
The study of Islamic ethics and moral philosophy has great significance in understanding the application of religious values and morality in individual and community life. In the Islamic tradition, ethics plays a role as a guide to behavior as well as a manifestation of the purpose of life to achieve happiness in the world and the hereafter that is blessed by Allah SWT. The concept of Islamic ethics is a concept that integrates the theory of obligation (deontology) and morality (morals). This concept integrates the theory of obligation (deontology) which focuses on moral rules and the theory of virtue (virtue ethics) which focuses on character development. This research aims to explore the relationship between the theories of obligation and virtue within the framework of Islamic ethics, as well as assess their relevance in addressing modern moral challenges, such as social justice, the environment, and politics. The approach used is qualitative with a literature study method, involving primary sources such as the Qur'an, Hadith, and classical Islamic literature, and comparing with Western moral theories. The results of the study show that Islamic ethics is holistic, uniting the obligations of Sharia with the development of noble morals. It offers flexible and universal moral guidance, is relevant to address global issues, and opens opportunities for constructive dialogue between Islamic ethics and contemporary moral philosophy.